Uso de activadores ruminales en el engorde de toretes mestizos charoles al sogueo, en la parroquia los encuentros, cantón Yantzaza, provincia de Zamora Chinchipe - Sarango Armijos, Andrés Bolívar (2022)
The aim of this research was to evaluate the effect of the 4% molasses-urea mixture, as a ruminal activator, during the fattening of Charol mestizo bulls in a grazing system in the Ecuadorian Amazon. The study was carried out for a period of 60 days, with 10 animals of 18 months of age and an average weight of 424 kg, distributed in two experimental groups of five animals each, by means of a completely randomised design. The treatments evaluated were: T1 rumen activator (4% molasses-urea), after an adaptation period of 10 days, and T2 control grazing only. The following variables were studied: bromatological composition of the pasture, feed intake, weight gain, feed conversion, profitability and cost-benefit ratio; analysis of variance and Tukey's test were carried out for each of the variables. The results showed high crude protein (CP) content of the tropical grasses (Setaria sphacelata and Echinochloa polystachya) with 13.9 and 15.2 %, respectively; although fibre content exceeded 35%. Treatment one (with supplementation) recorded higher feed intake (p≤0.001) with 14.0 kg DM d-1, higher average daily weight gain (1013 g; p≤0.001) and better feed conversion (14.0; p≤0.001); economic indicators were also better in treatment one. It is concluded that the use of the 4% molasses-urea mixture, as a rumen activator, improves technical and economic indicators in beef cattle under grazing conditions in the Ecuadorian Amazon. Key words: grazing, supplementation, molasses, urea, productive behaviour.